National groups of peasants in Belarus in the first half of the 19th century - Sosna, Vladimir (Balcanica Posnaniensia. Acta et studia, 2001)
The article presents the national and religious structure of the peasant population in the Belarusian lands during the first half of the nineteenth century. The author aims to demonstrate the impact of ethnic diversity on the social and legal status of various rural groups within the Russian Empire. The study employs a historical method based on the analysis of administrative records, legislation, and statistical data. The research shows that alongside the dominant Belarusian population there existed numerous groups distinguished by their origin or religion, including free peasants, German colonists, Old Believers, and foreign settlers. The author discusses the process of limiting the autonomy of the so-called “free people,” government policy toward colonists, and measures aimed at restructuring the social order of the countryside. The analysis demonstrates that ethnic and religious differences influenced tax obligations, legal rights, and relations with state authorities. The multiethnic character of the Belarusian countryside constituted one of its key features, while Russian policy sought gradually to standardize the status of various population groups while maintaining effective administrative control over the region.